Polymeric nanoparticles loaded with the 3,5,3´-triiodothyroacetic acid (Triac), a thyroid hormone: factorial design, characterization, and release kinetics - dos Santos KC (Dove Medical Press, 2012)
Karen C dos Santos,1 Maria Fatima GF da Silva,1 Edenir R Pereira-Filho,1 Joao B Fernandes,1 Igor Polikarpov,2 Moacir R Forim11Department of Chemistry, Federal University of Sao Carlos, Sao Carlos, 2Physics Institute of Sao Carlos, University of Sao Paulo, Sao Carlos, Sao Paulo, BrazilAbstract: This present investigation deals with the development and optimization of polymeric nanoparticle systems loaded with 3,5,3´-triiodothyroacetic acid (Triac). A 211–6 fractional factorial design and another 22 factorial design were used to study the contrasts on particle size distribution, morphology, surface charge, drug content, entrapment efficiency, and in vitro drug release profiles. The independent variables were the concentration of Triac, type and quantity of both polymer and oil, quantity of Span™ 60 and Tween® 80, volume of solvent and water, and velocity of both magnetic stirring and the transfer of the organic phase into the aqueous solution. The results of optimized formulations showed a narrow size distribution with a polydispersity index lower than 0.200. The particle sizes were on average 159.6 nm and 285.6 nm for nanospheres and nanocapsules, respectively. The zeta potential was higher than 20 mV (in module) and the entrapment efficiency was nearly 100%. A high-performance liquid chromatography method was developed, validated, and efficiently applied to Triac quantification in colloidal suspension. The main independent variables were the type and quantity of the polymer and oil. In vitro drug release profile depicted several features to sustain Triac release. Different formulations showed various release rates indicating an interaction between Triac and other formulation compounds such as polymer and/or oil quantity. Two different models were identified (biexponential and monoexponential) that allowed the control of both the release rate and Triac concentration. Thus, the prepared nanoparticles described here may be of clinical importance in delivering Triac for thyroid treatment.Keywords: Triac, nanoparticles, optimization, factorial design of experiments, HPLC analytical method